Tolerancia a suelos ácidos - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1985)
In 1984, CIAT continued the selection of bean germplasm tolerant to acid soils under low P and high Al conditions. A 3- stage screening system was used for bean lines from Central American adaptation nurseries, BGMV lines, pre-VEF lines, and advanced lines of the EP 84. Screening was done in random blocks with 4 replications, grouping the materials by growth habit and grain color, and protecting them against diseases and pests. The av. dry bean yield (at 14 percent MC) of the materials tolerant to acid soils are at the level of the controls Rio Tibaji and Carioca. (CIAT)